2020
DOI: 10.1101/2020.03.02.973578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular determinants and heterogeneity of tissue-resident memory CD8+T lymphocytes revealed by single-cell RNA sequencing

Abstract: One sentence summary: Here, we applied single-cell RNA-sequencing to elucidate the gene expression patterns of individual CD8 + T cells differentiating throughout the course of infection in the spleen and small intestinal epithelium, which revealed previously unidentified molecular determinants of tissue-resident T cell differentiation as well as functional heterogeneity within the tissue-resident CD8 + T cell population. Abstract: During an immune response to microbial infection, CD8 + T cells give rise to di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Moreover, trajectory analysis with TNF_T RM and STMN_T CM clusters revealed that TNF_T RM cells from two branches in an early state gradually progressed towards STMN1_T CM cells in a terminal state (Additional file 1: Figure S28A). T RM cells at the beginning of the trajectory expressed high levels of T RM markers, such as RUNX3, NR4A1, chemokines (CCL5) [59], and other T RM associated genes, including ID2 [60]. By contrast, T CM cells at the end of the trajectory were marked with expression of well-known T CM molecules, such as SELL and CCR7 (Additional file 1: Figure S28B).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, trajectory analysis with TNF_T RM and STMN_T CM clusters revealed that TNF_T RM cells from two branches in an early state gradually progressed towards STMN1_T CM cells in a terminal state (Additional file 1: Figure S28A). T RM cells at the beginning of the trajectory expressed high levels of T RM markers, such as RUNX3, NR4A1, chemokines (CCL5) [59], and other T RM associated genes, including ID2 [60]. By contrast, T CM cells at the end of the trajectory were marked with expression of well-known T CM molecules, such as SELL and CCR7 (Additional file 1: Figure S28B).…”
Section: Discussionmentioning
confidence: 99%
“…As such, KLRG1 lo CD127 hi cells are referred to as memory precursor T cells (MP cells) and KLRG1 hi CD127 lo cells as terminal effector T cells (TE cells). MP cells display enhanced multipotency compared with TE cells and more efficiently give rise to central memory T cells (T CM cells), effector memory T cells (T EM cells), and tissue-resident memory T cells (T RM cells; Kaech et al, 2003 ; Mackay et al, 2013 ; Milner and Goldrath, 2018 ); however, select TE cells are able to persist for several months after infection, forming a terminally differentiated T EM cell population (t-T EM cells) or long-lived effector population ( Kurd et al, 2020 ; Milner et al, 2020a ; Milner et al, 2020b ; Olson et al, 2013 ). Canonical transcription factors known to regulate antiviral T cell differentiation include Id3 ( Ji et al, 2011 ; Yang et al, 2011 ), TCF1 ( Zhou et al, 2010 ), Bcl6 ( Ichii et al, 2002 ; Liu et al, 2019 ), STAT3 ( Cui et al, 2011 ), and Foxo1 ( Kim et al, 2013 ; Hess Michelini et al, 2013 ; Utzschneider et al, 2018 ) as critical regulators of MP/T CM cells , and Id2 ( Cannarile et al, 2006 ; Knell et al, 2013 ; Masson et al, 2013 ), Zeb2 ( Dominguez et al, 2015 ; Omilusik et al, 2015 ; Omilusik et al, 2018 ), Blimp1 ( Kallies et al, 2009 ; Rutishauser et al, 2009 ), STAT4 ( Mollo et al, 2014 ), and T-bet ( Joshi et al, 2007 ) are required for more terminally differentiated populations.…”
Section: Introductionmentioning
confidence: 99%
“…This transcriptional profile is very similar to that of resident-memory T lymphocytes (T rm ) (Schenkel and Masopust, 2014). T rm cells are known to occupy other tissues including the lungs in humans; they are important for local immune response there and can serve as a functional link between the innate and adaptative immune system (Bedford et al, 2020; Kurd et al, 2020; Steinbach et al, 2018; Sun et al, 2019). While T rm occupancy in the NM has yet to be described in humans, T rm are known to occupy the NM in mice and help to prevent pulmonary dissemination of influenza virus (Pizzolla et al, 2017) This characterization of NM T cells demonstrates the potential insights gleaned by profiling NM samples across the lifespan.…”
Section: Resultsmentioning
confidence: 99%